2020
DOI: 10.1002/adma.201908435
|View full text |Cite
|
Sign up to set email alerts
|

A General Hypoxia‐Responsive Molecular Container for Tumor‐Targeted Therapy

Abstract: Enhanced drug delivery can improve the therapeutic efficacy of drugs and help overcome side effects. However, many reported drug‐delivery systems are too complex and irreproducible for practical use. In this work, the design of a hypoxia‐responsive molecular container based on calixarene, called CAC4A, which presents a significant advance in practical, hypoxia‐targeted drug‐delivery, is reported. CAC4A enables a wide variety of clinical drugs to be quantitatively loaded to improve their solubility and stabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
103
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 111 publications
(103 citation statements)
references
References 81 publications
0
103
0
Order By: Relevance
“…[1,2] Therefore,detecting and imaging hypoxia in living cells are not only important for accurate cancer diagnosis but also very useful for the evaluation of therapeutic effects. [3] Up to now,m any methods have been developed for sophisticated imaging methods of hypoxia, and two main approaches are involved. Thef irst approach focuses on the detection of reductive enzymes including nitroreductase and azoreductase resulting from an enhanced reductive stress upon hypoxia by nitro-or azo-containing fluorophores.…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] Therefore,detecting and imaging hypoxia in living cells are not only important for accurate cancer diagnosis but also very useful for the evaluation of therapeutic effects. [3] Up to now,m any methods have been developed for sophisticated imaging methods of hypoxia, and two main approaches are involved. Thef irst approach focuses on the detection of reductive enzymes including nitroreductase and azoreductase resulting from an enhanced reductive stress upon hypoxia by nitro-or azo-containing fluorophores.…”
Section: Introductionmentioning
confidence: 99%
“…[16] Unlike nanocarriers, macrocyclic molecules have well-defined molecular structure, precise cavity size and molecular weight, thereby batch-to-batch consistency can be guaranteed through strict manufacturing and careful quality control. [17] Moreover, these macrocyclic hosts load drugs via host-guest interactions with a defined stoichiometry (mostly 1:1) and a characteristic binding affinity, thereby enables quantitative drug loading…”
Section: Doi: 101002/adma202007719mentioning
confidence: 99%
“…[19] The upper rim of the calixarene was subsequentially modified with azophenyl and quaternary ammonium groups to obtain a cavity with enhanced affinity to a series of hydrophobic guest molecules due to the deeper cavitand and the formation of the charge interactions between the quaternary ammonium group and the anionic groups of the guest. [17] After obtaining QAAC4A-12C, the preparation of MASN was achieved by co-assembling QAAC4A-12C with PEG-12C in aqueous solution with a 1:1 molar ratio (details in Supporting Information). PEG-doping can improve the water-solubility of the QAAC4A-12C, make the hydration of MASN occurring easily under mild conditions, and more importantly, enhance the stability of the MASN during blood circulation to avoid undesired immune clearance.…”
Section: Combination Chemotherapy Refers To the Use Of Multiple Drugsmentioning
confidence: 99%
“…The integration of host-guest complexation and polymeric materials was employed for the fabrication of colloids, which could be further used in several applications. [115][116][117] For instance, Weck et al 118 reported the directional host-guest self-assembly of cyanine dyes-functionalized colloidal particles with telechelic BCPs attached to patchy particles. These colloidal particles could directionally assemble into longer and branched chains based on the selective heteroternary complexation of polymeric guests (MV 2+ and azobenzene) within the inner cavity of CB [8].…”
Section: Cucurbituril-based Mpsmentioning
confidence: 99%